2011
DOI: 10.1128/jvi.01160-10
|View full text |Cite
|
Sign up to set email alerts
|

Ebolavirus Proteins Suppress the Effects of Small Interfering RNA by Direct Interaction with the Mammalian RNA Interference Pathway

Abstract: Cellular RNA interference (RNAi) provides a natural response against viral infection, but some viruses have evolved mechanisms to antagonize this form of antiviral immunity. To determine whether Ebolavirus (EBOV) counters RNAi by encoding suppressors of RNA silencing (SRSs), we screened all EBOV proteins using an RNAi assay initiated by exogenously delivered small interfering RNAs (siRNAs) against either an EBOV or a reporter gene. In addition to viral protein 35 (VP35), we found that VP30 and VP40 independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 64 publications
3
106
0
1
Order By: Relevance
“…Thus, our results suggest that the microRNA-specific silencing suppression activity of VP35 observed in mammalian cells is not dependent on its ability to bind small RNAs. These results are consistent with a recent report that demonstrated the ability of the RISC-associated proteins PACT and TRBP to bind to EBOV VP35 when overexpressed by transfection (11). These investigators also reported that the VP35 interactions with PACT and TRBP were not dependent upon the presence of siRNA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our results suggest that the microRNA-specific silencing suppression activity of VP35 observed in mammalian cells is not dependent on its ability to bind small RNAs. These results are consistent with a recent report that demonstrated the ability of the RISC-associated proteins PACT and TRBP to bind to EBOV VP35 when overexpressed by transfection (11). These investigators also reported that the VP35 interactions with PACT and TRBP were not dependent upon the presence of siRNA.…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that both we ( Fig. 2A) and Fabozzi and colleagues (11) have observed that the silencing-independent translational enhancement caused by VP35 is much less than its effect on either microRNA-or siRNA-directed silencing, confirming the utility of the Fluc expression assays to measure microRNA-directed silencing suppression by VP35.…”
Section: Discussionsupporting
confidence: 79%
“…These transcomplementation assays confirm that RRE can act as an RSS in the context of a viral infection, similarly to what has been shown for other RSSs. 22,23,27 Because E1A is synthesized in part from the incoming DNA, 77 the increase of E1A expression from DVA adenovirus but not from WT adenovirus suggests that RRE mainly compensates for the lack of VA when the RNA is transcribed from the incoming DNA. The RRE-mediated increase in DNA replication observed on both DVA and WT adenovirus suggests that RRE further impacts the RNA transcribed from the replicating DNA whether it is mutated in VA or not.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The apparent absence of RNAi restriction of some viruses could be explained by the counteraction of encoded viral RNA silencing suppressors (RSSs). Several mammalian viruses encode RSSs, 17,[20][21][22][23][24][25][26][27][28][29] although the efficiency of a few of them has been debated. 16,[30][31][32] Proposed RSSs encoded by HIV-1 are the transactivator Tat 20,27 and the Trans Activation Response (TAR) RNA.…”
mentioning
confidence: 99%
“…Interestingly, interaction of PACT with VP35 prevents formation of a functional polymerase complex and suppresses viral RNA synthesis [102•]. In addition to antagonism of RIG-I signaling, VP35 was shown to inhibit RNA silencing [103,104] and the PKR-mediated cellular antistress response [105]. Since PACT is involved in both RNA silencing and PKR activation, it might be possible that the VP35-PACT interaction contributes to the suppression of RNA silencing and PKR-mediated antiviral response.…”
Section: Immune Evasionmentioning
confidence: 99%